2014
DOI: 10.1007/s00268-014-2674-0
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Prospective Study Comparing Acquisition of Laparoscopic Skills in Three‐Dimensional (3D) vs. Two‐Dimensional (2D) Laparoscopy

Abstract: Stereoscopic vision improved accuracy in laparoscopic skills for novices, which was manifested in reduced numbers of repetitions and errors. However, it does not affect the global performance time across all tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 31 publications
(60 reference statements)
1
74
2
1
Order By: Relevance
“…Most of these studies have been conducted using an experimental surgical model [19,25]. A recent review reported a lower rate (63% of the trials) of errors with the use of 3D system [9,26]. Storz P. et al [25] concluded that the use of 3D might be of minor importance in simple tasks, but it can increased task efficiency when performing difficult surgical tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have been conducted using an experimental surgical model [19,25]. A recent review reported a lower rate (63% of the trials) of errors with the use of 3D system [9,26]. Storz P. et al [25] concluded that the use of 3D might be of minor importance in simple tasks, but it can increased task efficiency when performing difficult surgical tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, laparoscopic hysterectomy was less preferred over the years. Previous studies did not reveal any significant benefits of laparoscopic hysterectomy when compared with VH; [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] however, most of these studies are outdated and as the TLH experience increases among gynecologists, the superiority of VH when compared with laparoscopic hysterectomy is slowly changing over time. [26] In a small sample size study conducted in Germany in 2007, it was observed that TLH takes longer compared with VH; however, it reduces the postoperative hospitalization duration and analgesic usage.…”
Section: Discussionmentioning
confidence: 97%
“…[18,19] Because of the previously experienced side effects while using 3D vision systems, i.e., a degraded viewing condition from poor image resolution, the requirement to wear uncomfortable glasses, and the system's high costs compared with 2D equipment, this technology may be less preferred. [10][11][12][13][14][15][16][17][18][19][20] The most important limitation of conventional laparoscopy is the lack of a sense of depth because of a 2D flat view of the surgical field. Surgeons are forced to rely on monocular vision to understand the 3D sense of open surgery; however, even the most experienced surgeons may face difficulties while performing complex surgical tasks such as tissue dissection and suturing under only 2D visualization.…”
mentioning
confidence: 99%
“…In two recent randomized prospective studies, 3D laparoscopy was shown to have a significant reduction of operative time and number of repetitive errors and improved accuracy of laparoscopic skills in novices [2,3] . It is also shown to reduce the learning curve of complex laparoscopic tasks on a prospective study [3].…”
Section: Discussionmentioning
confidence: 99%